The role of the government accounting system when moving from the traditional budget (items and expenditures budget) to programs and performance budget - Mohammed Abdullah/ Ibrahim Hicham/ Khalif QASEM KADEM HAMED ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
This research aims to explain the role of the government accounting system in Iraq when moving from the budget of items and expenditures to the budget of programs and performance, as Iraq is considered one of the countries with a rentier economy because it depends on the export of oil in drawing the country’s economic policies. Moreover, for decades Iraq depended on the preparation and implementation of the traditional budget (the budget of items and expenditures) in drawing financial and economic policies and relied on a government accounting system since 1976. This system is based on the system of accounting assets for 1940 and its amendments. These systems are not consistent with the size of the large transformation and transition in the Iraqi economy in light of applying the traditional budget that depends on the inputs without linking it to the outputs. By choosing the Baghdad Municipality (the new Baghdad municipality circle), a group of conclusions was obtained; the most important is the need to use the central style in dealing with expenses and revenues, which leads to an investigation’s obstruction of the budget goals, especially after the budget became decided and approved with large amounts that exceed (one hundred billion annually). The research reached a set of recommendations; the most important is the necessity of changing from the budget of the items and expenditures to the budget of programs and performance, as the traditional budget lacks control of programs and projects and its role in following up the performance, controlling efficiency and rationalizing financial spending. DOI /10.54633/2333-021-042-026